Serum C-reactive protein as independent prognostic variable in patients with ovarian cancer - Hefler, Lukas A; Concin, Nicole; Hofstetter, Gerda; Marth, Christian; Mustea, Alexander; Sehouli, Jalid; Zeillinger, Robert; Leipold, Heinz; Lass, Harald; Grimm, Christoph; Tempfer, Clemens B; Reinthaller, Alexander (Clinical cancer research, 2008)
To evaluate serum C-reactive protein (CRP) as prognostic variable in patients with epithelial ovarian cancer (EOC). In a multicenter study, preoperative serum CRP was evaluated in 623 patients with EOC. Results were correlated with clinical data. Mean (SD) preoperative serum CRP was 3.6 (4.8) mg/dL. Serum CRP was significantly associated with International Federation of Gynecologists and Obstetricians stage (P < 0.001) and postoperative residual tumor mass (P < 0.001) but not with histologic grade (P = 0.1) and type (P = 0.7), patients' age (Pearson's correlation coefficient = 0.05; P = 0.2), and serum CA 125 (Pearson's correlation coefficient = 0.02; P = 0.6). Patients with platinum-resistant EOC had significantly higher CRP serum levels compared with patients with platinum-sensitive EOC [6.0 (6.6) mg/dL versus 2.8 (3.8) mg/dL; P < 0.001]. Higher International Federation of Gynecologists and Obstetricians stage (P < 0.001), presence of postoperative residual tumor mass (P < 0.001), tumor grade (P = 0.001), serum CA 125 (P = 0.03), and serum CRP (P = 0.001) were independently associated with overall survival. Patients with serum CRP < or =1 mg/dL versus >1 mg/dL had an overall 5-year survival of 82% versus 58.5% (P < 0.001). Serum CRP can be seen as a novel, widely available independent prognostic variable of ovarian cancer.